2006
DOI: 10.1111/j.1439-0426.2006.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of cryptic reef fishes from the southwestern Gulf of California, Mexico

Abstract: Length-weight relationships of 33 cryptic reef fishes from the southwestern Gulf of California were estimated. The most common families were Gobiidae (seven species), Labrisomidae (four), Pomacentridae (three), and Tripterygiidae (three). These are the first length-weight parameters reported for 32 of these species. Specimens were sampled during a comparative ecological study of community structure of fish assemblages associated with coral heads, rocky walls, and artificial reefs in Bahı´a de La Paz, Baja Cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 8 publications
(8 reference statements)
0
23
1
2
Order By: Relevance
“…Our present estimate (b = 2.618) again indicates a negative allometric relation in the king angelfi sh, and coincides with the general pattern depicted by the family. It is possible that the results of Balart et al (2006) are different from our results due to the small sample size examined by those authors (only 44 individuals, compared to the 794 in our sample).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our present estimate (b = 2.618) again indicates a negative allometric relation in the king angelfi sh, and coincides with the general pattern depicted by the family. It is possible that the results of Balart et al (2006) are different from our results due to the small sample size examined by those authors (only 44 individuals, compared to the 794 in our sample).…”
Section: Discussioncontrasting
confidence: 56%
“…Regarding the genus Holacanthus- Marks and Klomp (2003) described b values lower than 3 in Holacanthus bermudensis Goode, 1876 (2.89), Holacanthus ciliaris (Linnaeus, 1758) (2.90), and Holacanthus tricolor (Bloch, 1795) (2.85). Finally, there is only one study in reference to the Eastern Tropical Pacifi c, performed on angelfi sh- Balart et al (2006). Those authors found an allometric relation between weight and length, but it was positive, that is, a greater relative increase in weight with respect to length (b = 3.08).…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers on length–weight relationship (LWR) for fishes of Baja California Peninsula, Mexico include González‐Acosta et al. (2004), Balart et al. (2006) and Ruiz‐Campos et al.…”
Section: Introductionmentioning
confidence: 99%
“…The Cortés and Oceanic Island provinces exhibit the lowest values of functional evenness ( J ′ < 0.6, Figure d), and consequently, their values of functional diversity were low ( H ′ < 0.44). This is probably a consequence of a concentration of biomass in the groups with high trophic levels (schools of large carnivores, such as Sphyrna lewini and Caranx sexfasciatus ), which are quite common in Revillagigedos, Malpelo and Cocos (Oceanic Islands province), and in Cabo Pulmo (Cortés province), as well as schooling of reef‐associated fish ( Haemulon steindachneri, Anisotremus interruptus and Prionurus laticlavius ) and sea stars (functional group F6), which are abundant in the Gulf of California (Balart et al., ; Reyes Bonilla & González Azcárraga, ; Thomson, Findley, & Kerstitch, ).…”
Section: Discussionmentioning
confidence: 99%
“…and Caranx sexfasciatus), which are quite common in Revillagigedos, Malpelo and Cocos (Oceanic Islands province), and in Cabo Pulmo (Cortés province), as well as schooling of reef-associated fish (Haemulon steindachneri, Anisotremus interruptus and Prionurus laticlavius) and sea stars (functional group F6), which are abundant in the Gulf of California(Balart et al, 2006;Reyes Bonilla & González Azcárraga, 2005; …”
mentioning
confidence: 99%